6
$\begingroup$

I have a limit:

$$\lim_{x \to \infty} \left(\sqrt{x^4+5x^2+1} - x^2\right)$$

I know the answer is $\frac{5}{2}$, and you can get it by multiplying and dividing both sides by the conjugate ($\sqrt{x^4+5x^2+1} + x^2$) to get

$$ \lim_{x \to \infty} \left(\frac{x^4+5x^2+1-x^4}{\sqrt{x^4+5x^2+1} + x^2}\right) = \lim_{x \to \infty} \left(\frac{5x^2+1}{x^2 \sqrt{1+\frac{5}{x^2}+\frac{1}{x^4}} + x^2}\right) $$

It is then pretty easy to see that the stuff under the square root in the denominator will go to 1, and we will get $\frac{5x^2}{2x^2}$ = $\frac{5}{2}$. This seems to be the correct answer according to WolframAlpha as well. However, I got to thinking that there seems to be another completely legitimate way to do this limit, as follows:

$$ \lim_{x \to \infty} \left(\sqrt{x^4+5x^2+1} - x^2\right) = \lim_{x \to \infty} \left(x^2 \left(\sqrt{1+\frac{5}{x^2}+\frac{1}{x^4}}\right) - x^2\right) $$

Again, the stuff inside the square root will go to 1, so we will get

$$ = \lim_{x \to \infty} \left( x^2 - x^2\right ) = 0$$

Obviously this second way is wrong, but can someone explain why?

$\endgroup$
0
8
$\begingroup$

You made a step which does not follow from your previous equations. For example, $$1=\lim_{x\to \infty} (x^2+1-x^2)=\lim_{x\to \infty} (x^2(1+x^{-2})-x^2)\neq \lim_{x\to \infty}(x^2-x^2)=0$$

This shows straightforwardly that such a manipulation isn't valid without extra justification.

$\endgroup$
0
6
$\begingroup$

Writing $$ \lim_{x \to \infty} \left(\sqrt{x^4+5x^2+1} - x^2\right) = \lim_{x \to \infty} \left(x^2 \left(\sqrt{1+\frac{5}{x^2}+\frac{1}{x^4}}\right) - x^2\right) $$ is fine, but you cannot ignore what is inside the radical.Remember that, for small value of $y$, $\sqrt{1+y}$ has a Taylor expansion which is $1+\frac{y}{2}+O\left(y^2\right)$. If we ignore the third term is the radical (wich is much smaller that the second), we then have $$\sqrt{\frac{1}{x^4}+\frac{5}{x^2}+1}=1+\frac{5}{2 x^2}+O\left(\left(\frac{1}{x}\right)^4\right)$$
Expanding now, we find again the correct limit.

$\endgroup$
1
$\begingroup$

The second method is wrong as it results in an indeterminate form. If I write the last term as \begin{equation} x^2\left(\sqrt{1 + \frac{5}{x^2} + \frac{1}{x^4}} - 1\right). \end{equation} After putting the limiting value of $x$ I get $x^2$((a term that tends to $1$ but is greater than $1)-1)$ or $ \infty $*(a number tending to $0)$. Hence an indeterminate form.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.